Penerapan Transit-Oriented Development (TOD) terhadap Bus Rapid Transit (BRT) sebagai Penunjang Pertumbuhan Ekonomi berbasis Wisata pada Kawasan Metropolitan Joglosemar - Kishandoko, Irham Annafi; Risna, Anandharu; Ramadhanti, Jasmine Akhiru (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2025)
The Joglosemar Metropolitan Area (JMA) is a National Strategic Economic Zone that plays a crucial role in driving regional economic growth based on tourism. Despite having high tourism and economic potential, this region still faces challenges in the form of limited connectivity and integration of the transportation system between tourism centers. This study aims to formulate a Trans Joglosemar Bus Rapid Transit (BRT) planning innovation through a Transit-Oriented Development (TOD) approach to optimize the growth of a competitive and sustainable tourism sector. The research method employs a quantitative approach with spatial analysis and policy review. The results indicate that the development of the TOD-based Trans Joglosemar BRT has the potential to enhance accessibility and connectivity between tourist destinations, thereby facilitating the movement of KMJ tourists. The integration of BRT stations as connectivity hubs for tourists stimulates economic growth in the tourism sector. Furthermore, applying the TOD concept to the Trans Joglosemar BRT planning contributes to reducing dependence on private vehicles and supports the principles of sustainable urban development. This study concludes that the innovative planning of the Trans Joglosemar BRT with a TOD approach is an effective strategy for strengthening regional connectivity, enhancing tourism competitiveness, and supporting sustainable economic growth in the Joglosemar Metropolitan Area (JMA).